Comparative effectiveness and safety of antipsychotic drugs in schizophrenia treatment: a real‐world observational study. (12th July 2016) - Vanasse, A.; Blais, L.; Courteau, J.; Cohen, A. A.; Roberge, P.; Larouche, A.; Grignon, S.; Fleury, M.‐J.; Lesage, A.; Demers, M.‐F.; Roy, M.‐A.; Carrier, J.‐D.; et al.
Abstract : Objective: The objective was to compare, in a real‐world setting, the risk of mental and physical health events associated with different antipsychotic drugs (clozapine, olanzapine, risperidone, quetiapine and first‐generation antipsychotics) in patients with SZ. Methods: This is a retrospective cohort study using administrative data. Outcome measures included any mental health event (suicide, hospitalization or emergency visit for mental disorders) and physical health event (death other than suicide, hospitalization or emergency visit for physical disorders). Cox proportional hazard models were used to estimate the hazard ratios of the events associated with the use of the different antipsychotic drugs. Results: The cohort included 18 869 adult patients living in the province of Quebec (Canada) with SZ and starting antipsychotic drugs between January 1998 and December 2005. Results show that quetiapine and not using any antipsychotics were associated with an increased risk of mental and physical health events as compared to other drugs. The second finding is the confirmation of better performance of clozapine. The results were robust across sensitivity analyses. Conclusion: Both findings call for an international public health and drug agencies surveillance of 'real‐world' antipsychotic medication to ensure the optimal choices in treatment guidelines for SZ.